h(x)=(0)2+3x+-18

Simple and best practice solution for h(x)=(0)2+3x+-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for h(x)=(0)2+3x+-18 equation:


Simplifying
h(x) = (0) * 2 + 3x + -18

Multiply h * x
hx = (0) * 2 + 3x + -18

Multiply 0 * 2
hx = 0 + 3x + -18

Anything times zero is zero.
hx = 0 + 3x + -18

Reorder the terms:
hx = 0 + -18 + 3x

Combine like terms: 0 + -18 = -18
hx = -18 + 3x

Solving
hx = -18 + 3x

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Divide each side by 'x'.
h = -18x-1 + 3

Simplifying
h = -18x-1 + 3

Reorder the terms:
h = 3 + -18x-1

See similar equations:

| 5x-13=4x | | -22+2n=-8(3n+7) | | 5x+3y-4=30 | | log(7-12x)=2 | | 1+3y-y=y-4+2y | | 5y+3y-4=30 | | 6.2x+7.1x-y= | | Y=40x+-16x^2 | | .4y+7.96=2.24 | | (x+4y^2)dy+(y+x^2)dx=0 | | 28x^2-9x-1=0 | | 3x+13=-3x+73 | | (2v+14)(v^2-8v+12)=0 | | 14t+15=10t+31 | | 8x-1=642x | | 2t-7=t+2 | | z^2+(4+i)*z-6+6i=0 | | 6h+20=720 | | 2b-50+b+2b-2+30+b-25+44+b-22=360 | | 2n-15=45 | | -3(4+2)=4-22 | | 4n+12=7n+9 | | 3w-23+3w-33+4w+4w-46+49+3w-39+61=360 | | 2x*2x-9x+2=0 | | 2x+2(3x+1)+3x-1=7x+1 | | 6x+6=6x-5 | | 2x+45=x-32 | | 60.5+90+x=180 | | 3w-23+3w-33+4w-46+3w-39+49+61=360 | | 6(x+1)-(p+1)=6x+3 | | 7k^3+2x=0 | | 12s=16+6s+19 |

Equations solver categories